La llengua de Carles Riba: el cas de Guillot, bandoler. - TURULL, ISABEL (Scripta, 2015)
As a part of a sistematic study on Carles Riba's language, we analyse in this paper one of his first short stories. Guillot, bandoler represents the author's first attempt to write a children's tale: it was published in 1918, in a moment when Fabra's works on Catalan's orthography and normative were still evolving. It presents, thus, a language that tends to correctness but that is also spontaneous, while we can link some of its characteristic features to the author's will of adhering to a concrete literary genre. The tale's tradition allows the presence of terms that belong to a more elevated language in a context of literary mymesis of the spoken language, and that would justify the presence in this text of expressions like: «pujaven [...] tan instruïdets»; next to: «la bellica munió».